Percutaneous closure of the patent ductus arteriosus: opportunities moving forward. (27th February 2019) - Mitchell, Courtney C.; Rivera, Brian K.; Cooper, Jennifer N.; Smith, Charles V.; Berman, Darren P.; Slaughter, Jonathan L.; Backes, Carl H.
Abstract: The optimal treatment method for infants with a patent ductus arteriosus (PDA) necessitating closure remains a subject of controversy and debate. While the risks associated with surgical PDA ligation are well described, the available evidence base for alternative management strategies during infancy, including percutaneous closure or conservative (nonintervention) management, are not well explored. Among infants, the goals of this review are to: (a) use rigorous systematic review methodology to assess the quality and quantity of published reports on percutaneous closure vs surgical ligation; (b) compare outcomes of percutaneous closure vs conservative management; and (c) based on recommendations from the International PDA symposium, to elucidate needs and opportunities for future research and interdisciplinary collaboration. The available evidence base, as well as on broad consensus reached at the International PDA Symposium, suggests that a contemporary, pragmatic clinical trial comparing PDA treatment strategies is warranted. Additionally, quality assurance safeguards are necessary in the implementation of newer PDA closure devices. Finally, to determine best approaches to treatment for infants with PDA, tools for consistent data collection and reporting across centers and disciplines are needed to minimize heterogeneity and permit pooled analysis.